2015
DOI: 10.1038/ejhg.2014.282
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive prenatal testing using a novel analysis pipeline to screen for all autosomal fetal aneuploidies improves pregnancy management

Abstract: Noninvasive prenatal testing by massive parallel sequencing of maternal plasma DNA has rapidly been adopted as a mainstream method for detection of fetal trisomy 21, 18 and 13. Despite the relative high accuracy of current NIPT testing, a substantial number of false-positive and false-negative test results remain. Here, we present an analysis pipeline, which addresses some of the technical as well as the biologically derived causes of error. Most importantly, it differentiates high z-scores due to fetal trisom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
148
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(154 citation statements)
references
References 54 publications
3
148
0
Order By: Relevance
“…Follow‐up case studies of false‐positive NIPT results has identified a variety of potential causes including a vanishing twin, unidentified maternal tumors, maternal mosaicism, and confined placental mosaicism . More recently, several groups using different NIPT methodologies have reported maternal copy number variations (CNVs) as an additional cause of false‐positive NIPT results . In order to further investigate the potential contribution of maternal CNVs to false‐positive NIPT results, we performed NIPT on a large cohort of 112 021 pregnant women using low coverage massively parallel sequencing and analyzed the 74 false‐positive trisomy samples for the presence of maternal CNVs.…”
Section: Introductionmentioning
confidence: 99%
“…Follow‐up case studies of false‐positive NIPT results has identified a variety of potential causes including a vanishing twin, unidentified maternal tumors, maternal mosaicism, and confined placental mosaicism . More recently, several groups using different NIPT methodologies have reported maternal copy number variations (CNVs) as an additional cause of false‐positive NIPT results . In order to further investigate the potential contribution of maternal CNVs to false‐positive NIPT results, we performed NIPT on a large cohort of 112 021 pregnant women using low coverage massively parallel sequencing and analyzed the 74 false‐positive trisomy samples for the presence of maternal CNVs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there are already reports on genome-wide NIPT analysis with promising results [2,3]. For trisomy 13,18, and 21 screening, the test performs much better than the traditional first trimester screening (combined test) [1].…”
Section: Biological Origin Of False Positive Niptmentioning
confidence: 99%
“…However, in order to avoid the abortion of an unaffected fetus it then will be necessary not only to rely on z-scoring, but to use an analysis pipeline that allows whole chromosome analysis. This enables differentiation of high z-scores due to fetal trisomy from those caused by maternal CNVs [2,46,47]. Moreover, also other causes of false positive NIPT results, such as maternal mosaicism or a vanishing twin, should be excluded in such cases before TOP may be considered.…”
Section: Five-year Viewmentioning
confidence: 99%
“…[4][5][6] We optimized a large parallel sequencing-based NIPT dataset and analysis, which not only interrogates the common trisomies but also allows the genomewide discrimination of fetal and maternal segmental aneuploidies. 3 All patients undergoing NIPT consented to release of information for study purposes beyond trisomy 13, 18, and 21; this consent and the study protocol were approved by the University Hospitals, Leuven ethical board. Of the first 4000 prospective NIPT samples, we identified 3 profiles with an aberrant quality score and reproducible genomewide representation (GR) profiles reminiscent of cancer-related copy number variation.…”
mentioning
confidence: 99%